Diversity in the oesophageal phenotypic response to gastro-oesophageal reflux: immunological determinants. Issue 4 (1st April 2002) - Fitzgerald, R C; Onwuegbusi, B A; Bajaj-Elliott, M; Saeed, I T; Burnham, W R; Farthing, M J G
Abstract : Background and aims: Approximately 10% of adults experience gastro-oesophageal reflux symptoms with a variable oesophageal response. A total of 60% have no endoscopic abnormality, 30% have oesophagitis, and 10% have Barrett's oesophagus. We investigated whether the inflammatory cell infiltrate and cytokine profiles of these clinical phenotypes merely vary in severity or are fundamentally different. Methods: Patients with reflux symptoms and a normal oesophagus (n=18), oesophagitis (n=26), and Barrett's oesophagus (n=22 newly diagnosed, n=28 surveillance) were recruited. Endoscopic and histopathological degrees of inflammation were scored. Cytokine expression was determined by competitive reverse transcriptase-polymerase chain reaction and immunohistochemistry. Results: In oesophagitis, endoscopic and histopathological grades of inflammation correlated highly. mRNA expression of proinflammatory interleukin (IL)-1β, IL-8, and interferon γ (IFN-γ) were increased 3–10-fold compared with non-inflamed squamous or Barrett's oesophageal samples. There was a modest increase in anti-inflammatory IL-10 but no increase in IL-4. In Barrett's oesophagus, 29/50 had no endoscopic evidence of inflammation and histopathological inflammation was mild in 17/50 and moderate in 24/50, independent of acid suppressants. Expression of IL-1β, IL-8, and IFN-γ was similar to non-inflamed squamous mucosa. IL-10 was increased 1.6-fold similar to oesophagitis. IL-4 was increased fourfold, with 100-fold increase in IL-4/T cell receptor expression, compared with squamous oesophagus or oesophagitis. Conclusions: Barrett's oesophagus is characterised by a distinct Th-2 predominant cytokine profile compared with the proinflammatory nature of oesophagitis. The specific oesophageal immune responses may influence disease development and progression.